Gender in lift irrigation schemes in East Gujarat, India - Saini, H.; van Koppen, Barbara (International Water Management Institute, 2001)
This study highlights the gender aspects of a community-based irrigation program supported by the NGO, Sadguru. It focuses on the intra-household organization of irrigated agriculture, the gender dimensions of scheme-level irrigation management, and Sadguru's efforts to strengthen women's participation in irrigation cooperatives.